1988
DOI: 10.1098/rstb.1988.0102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variation in vector-borne plant viruses: epidemiological significance

Abstract: Patterns of variation are examined in four groups of plant viruses, with special reference to their particle proteins and to changes in vector transmissibility and specificity. In the nepoviruses and potyviruses, non-circulative transmission, by nematodes and aphids respectively, seems dependent on structural features on the surface of the virus particles. The N-terminal part of the particle protein may play the key role in potyviruses. Similarly in the luteoviruses, and possibly in the geminiviruses, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…Thus, it is becoming clear that in several virus groups vector transmission is governed by interactions between virus particle proteins and virus-encoded proteins, which are not needed for the integrity of the virus particles. The extensive evidence that coat protein plays an important role in transmission (Harrison & Murant, 1984;Harrison & Robinson, 1988) is therefore only part of the story.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is becoming clear that in several virus groups vector transmission is governed by interactions between virus particle proteins and virus-encoded proteins, which are not needed for the integrity of the virus particles. The extensive evidence that coat protein plays an important role in transmission (Harrison & Murant, 1984;Harrison & Robinson, 1988) is therefore only part of the story.…”
Section: Discussionmentioning
confidence: 99%
“…Three distinct groups of species of cassava-infecting whitefly-transmitted geminiviruses (WTGs, genus Begomovirus) have been distinguished based on their nucleotide sequences (Stanley & Gay, 1983 ;Hong et al, 1993 ;Zhou et al, 1997) and by their reactions with a panel of monoclonal antibodies (Harrison & Robinson, 1988 ;Swanson & Harrison, 1994). Group A, African cassava mosaic virus (ACMV), is found in West Africa, including Burundi, the western parts of Kenya, Chad, Uganda and recently, Cameroon (Fondong et al, 1998).…”
Section: Complete Nucleotide Sequences Of the Dna-a (2800 Nt) And Dnamentioning
confidence: 99%
“…The probable role of recombination in geminivirus evolution in the short to medium term is discussed. Harrison & Robinson, 1988 ;Swanson & Harrison, 1994). Comparisons of the nucleotide sequences of the complete genomes (DNA-A and DNA-B) of isolates representing two of these categories (Stanley & Gay, 1983 ;Hong et al, 1993), and of part of DNA-A of an isolate in the third category, indicated that the isolates are not closely related and should be regarded as three separate species, which were named African cassava mosaic virus (ACMV), East African cassava mosaic virus (EACMV) and Indian cassava mosaic virus (ICMV) (Hong et al, 1993).…”
Section: Introductionmentioning
confidence: 99%